PENGARUH PRETREATMENT HIDROLISIS ASAM TERHADAP PENINGKATAN PRODUKSI BIOGAS DARI ENCENG GONDOK (Eichornia crassipes) MENGGUNAKAN BIOSTARTER SLUDGE BIODIGESTER AKTIF - , RAUDATI HILDAYATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Water hyacinth is a lignocellulosic material with high cellulose content and a complex compound which is difficult to be described, so it can slow the rate of biogas formation. To facilitate the disintegration of compound cellulose into simple sugars that can be utilized in the biogas formation, it is necessary to pretreatment toward water hyacinth. One of the pretreatment to do is using acid hydrolysis. This research aims to study the effect of concentration of H2SO4 addition as a catalyst in the hydrolysis process and the length of time the hydrolysis toward the cellulose degradation and glucose formation. In addition, this research also studies the effect of pretreatment on water hyacinth toward increasing of biogas production with the addition of active sludge biodigester as biostarter. This research is conducted in two stages, the first stage is the hydrolysis process with variation concentration of H2SO4 96% addition as much as 0%, 1%, 2%, 3%, 4% and 5% (v/v) reacted in an autoclave at a temperature of 121 oC and permanent pressure 2.0 atm for 60 minutes. Further ,it is done hydrolysis with time variation, i.e.: 0 minutes, 30 minutes, 45 minutes, 60 minutes, 75 minutes and 90 minutes. The second stage is the fermentation process slurry of water hyacinth. The hydrolysis results are added by an active sludge biodigesteras biostarter. The fermentation process is done by batch scheme in biodigester as a form of erlenmeyer 1000 ml. The results of this research show that the highest efficiency of cellulose degradation obtained 65.5% by the addition of 96% H2SO4 concentration of 5%. In this stage of hydrolysis with time variation, the highest efficiency of cellulose degradation is resulted in 90 minutes of 79.1%. However, the increase of highest glucose content is at 45 minutes of 9.2% from the initial glucose content. Biogas production from water hyacinth that has been pretreatment added the active sludge biodigester increases of 2.5 times of the material without pretreatment. The highest accumulation of biogas obtained at B7 biodigester for 450.4 mL by the addition of 96% H2SO4 concentration of 5% within 90 days and the result of methane content is 69.8% measurements on day-88.